Comparison of the effectiveness of 3 irrigation devices for the cleaning of root canal walls instrumented with oscillatory and rotary techniques - De Souza Ferreira, Nadia; Ribeiro Camargo, Carlos Henrique [UNESP]; Palo, Renato Miotto; Martinho, Frederico Canato; Gomes, Ana Paula Martins [UNESP] (My University, 2015)
In this study, scanning electron microscopy (SEM) was used to evaluate the smear layer removal of 3 irrigation devices. The study hypothesis was that more contemporary side-vented needles and brush-covered needles are more efficient for smear layer removal of root canals than traditional needles. The aim of this study was to compare the effectiveness of these irrigation devices in the cleansing of root canals instrumented with oscillatory and rotary systems. Sixty single-rooted teeth were divided according to instrumentation and irrigation techniques into 6 groups. The teeth were prepared for SEM analysis to evaluate the cleansing of cervical, middle, and apical thirds. For all groups, the cleansing of the cervical and middle thirds was better than that of the apical third (P < 0.05). Regardless of the instrumentation technique, no statistically significant differences were found between the groups regarding the cleansing of root canal walls (P > 0.05).
Keywords: Endodontics; Irrigation; Root canal preparation; Scanning electron microscopy; Smear layer